Requirement analysis of protection of future MV & LV DC grid - Lee, Kok Cheung (2016)
High-voltage (>65 kV) direct current (HVDC) transmission line has been adopted in many countries such as China, US and Russia for many years, for lower electrical losses, Iess capital costs, ease of control, etc. With the rapidly growing of HVDC system, researcher and electrical engineer had started to consideration for medium and the Iow voltage (MV/LV) DC distribution grid. Unlike the HVDC, the MV/LVDC distribution is a new distribution concept, and requires more research prior implement. A well established DC based power protection system could become one of the major topic; requiring detail studies during the conceptual planning and design stage. This MSc thesis is aimed for detailed investigation about the requirements of the protection of future MV/LVDC grids for the distribution side.